THE RELEVANCE OF PRICE, LIFESTYLE, AND SOCIAL MEDIA TOWARDS PURCHASE DECISIONS OF MOTATO PRODUCT - Clyde Morita Halim; J.E. Sutanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The research entitled “The effect of price, lifestyle, and social media on purchasing decisions for Motato products” has three objectives, namely: (1) Knowing the effect of price on Motato consumer purchasing decisions, (2) Knowing the influence of lifestyle on Motato product purchasing decisions, (3) Knowing the influence of social media on the decisions to purchase Motato. Motato is a business that is engaged in food made from mashed potatoes. Sales made by Motato are online and selling at existing bazaars. This study uses quantitative methods. The population in this study are all consumers who have bought Motato products and who are followers on Motato's social media accounts. The sample in this study amounted to 140 respondents. Collecting data using a questionnaire that is distributed online. In this study, the data obtained were processed using multiple linear regression analysis using the SPSS program as a tool. The results of this study are: (1) price has a significant effect on Motato's consumer purchasing decisions. (2) lifestyle has a significant effect on purchasing decisions for Mototo products. (3) Social media has a significant effect on purchasing decisions for Mototo products. Keywords: consumer motto, lifestyle, social media, product motto